2022
DOI: 10.48550/arxiv.2207.03506
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing the Collisionless Nature of Dark Matter with the Radial Acceleration Relation in Galaxy Clusters

Abstract: The radial acceleration relation (RAR) represents a tight empirical relation between the inferred total and baryonic centripetal accelerations, g tot = GM tot (< r)/r 2 and g bar = GM bar (< r)/r 2 , observed in galaxies and galaxy clusters. The tight correlation between these two quantities can provide insight into the nature of dark matter. Here we use BAHAMAS, a state-of-the-art suite of cosmological hydrodynamical simulations, to characterize the RAR in cluster-scale halos for both cold and collisionless d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…The discrepancy is so large that it cannot be explained by either the possible biases or systematics in our analysis, such as the uncertainty in stellar mass and hydrostatic bias, or the 0.12 dex scatter in the McGaugh et al (2016) relation. This is in broad agreement with the results for X-COP clusters (Eckert et al 2022) and BAHAMAS simulation (Tam et al 2022). Due to the removal of the core, we have no constraints on g bar at high acceleration, where Eckert et al (2022) observed that the RAR of X-COP clusters eventually catched up with the McGaugh et al (2016) relation for galaxies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The discrepancy is so large that it cannot be explained by either the possible biases or systematics in our analysis, such as the uncertainty in stellar mass and hydrostatic bias, or the 0.12 dex scatter in the McGaugh et al (2016) relation. This is in broad agreement with the results for X-COP clusters (Eckert et al 2022) and BAHAMAS simulation (Tam et al 2022). Due to the removal of the core, we have no constraints on g bar at high acceleration, where Eckert et al (2022) observed that the RAR of X-COP clusters eventually catched up with the McGaugh et al (2016) relation for galaxies.…”
Section: Discussionsupporting
confidence: 90%
“…Not only is the normalization of acceleration higher than what is found for galaxies (e.g., Tian et al 2020), but also the overall shape of the observed cluster RAR clearly deviates from the model in Eq. 4, implying a completely different RAR between clusters and galaxies (e.g., Eckert et al 2022;Tam et al 2022).…”
Section: Discussionmentioning
confidence: 99%